TINJAUAN YURIDIS TENTANG GABUNGAN TINDAK PIDANA SEBAGAI HAL YANG MEMBERATKAN PIDANA Studi Kasus: Putusan Perkara Nomor:141/Pid.B/2018/PN Mrj (Pencurian) - Failin, Failin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
In criminal law there is no penalty if there is no wrongdoing, this basis is about the accountability of a person for the actions he has done. Therefore, in criminal law there are exceptions to such criminal liability, for example contained in Articles 48, 49, 50 and so forth. In addition, there are burdensome things that will be imposed on the accused for crimes committed, such as samenloop, recidive and so on. In the Muaro Sijunjung District Court there is one case concerning a combination of criminal acts, namely theft crimes accompanied by violence and moreover this theft is carried out among families (theft in the family). In this case the judge has decided the prison sentence for 6 (six) Years. But according to the analysis of the author there is no sense of justice for the victim because this perpetrator is the husband of the victim's child so that there is no deterrent effect for the perpetrator, the reason that there is no more theft in this family because no matter how small the crime committed by a person must be taken action in order to obtain justice and legal certainty. In principle, judges have the freedom to determine the measure of punishment to be imposed on the perpetrators of crimes, as long as it does not exceed the maximum provisions specified in the Criminal Code. Therefore, the sentencing of the accused for a combination of crimes committed by means of pure absorption Stelsel that is If a person commits several acts that are several delik each threatened with a different kind of criminal